Isolated pneumopericardium after blunt chest trauma - Guidi, Gonçalo; Silva, Silvia; Pinto-de-Sousa, Joao; Prospero-Luis, Fernado; Vaz-Pereira, Ricardo; Fernandes, Urania; Martins, Daniela; Leal, Clara; Vieira, Bruno; Freitas, Francisca; Marques, Carolina (International Surgery Journal, 2022)
Pneumopericardium after blunt chest trauma it’s a very rare entity in adults, usually seen in association with pneumothorax or pneumomediastinum. When isolated, it’s believed to be caused by the Macklin effect. Generally, it’s a benign, self-limiting condition requiring no additional therapy. However, it must be recognized because an increase in intrapulmonary pressure (example- intubation) can lead to a tension pneumopericardium or cardiac tamponade.